The Influence Health Promotion Against Understanding Family on Reproductive Health Young Women - Seri Wahyuni Harahap; Kiki Khoiriyani; Eni Monaliska Sihombing; Ayu Ulfah Nur Lubis (International Journal of Public Health Excellence (IJPHE), 2022)
In Indonesia, shift score about attitude as well as knowledge about reproduction has happened. this caused less youth _ get knowledge as well as information about health reproduction that has risk enough tall from behavior that is n't in accordance with hope. Youth which is the period where they start experience change physical, physiological Emotional and also psychic are also connected with change social and moral happenings. Teenager need get correct, clear and complete information about health reproduction them. Knowledge and attitude about health reproduction of course must mastered before take life family. Destination from study the to use knowing influence promotion health reproduction to level knowledge as well as attitudes sexual teenager daughter. Method study preexperiment this use one group pretest posttest design. Instrument study use questionnaire. Data will analyzed with method univariate as well as bivariate using the Wilcoxon test. Based on results study said, stated that promotion health reproduction enough have influence to understanding family related reproduction teenager daughter.